Проект відділення олігомеризації фракції С9 продуктивністю 7000 т/рік - Томков, Тарас Олегович; Tomkov, Taras Olehovych (Національний університет "Львівська політехніка", 2024)
У роботі представлено дослідження з розробки технології синтезу нафтополімерних смол (НПС) з фракції С9 – побічного продукту піролізу вуглеводнів, що містить ароматичні ненасичені компоненти. Актуальність роботи зумовлена потребою в створенні імпортозаміщуючих матеріалів з покращеними експлуатаційними характеристиками, які можуть застосовуватись у лакофарбовій, гумовій, паперовій і будівельній промисловості [1, 2]. Основним джерелом сировини для виробництва вуглеводневих смол є рідкі продукти піролізу (РПП), зокрема легка фракція (до 473 К), що включає цінні компоненти С5 і С9, здатні до полімеризації. Вказано, що вміст активних мономерів (стирол, інден, дициклопентадієн тощо) у таких фракціях може досягати 30–40?% маси, що робить їх ефективною основою для синтезу коолігомерів [3]. За типом вуглеводнів у сировині олігомери можна класифікувати: ? Ароматичні смоли, отримані з алкенілароматичних вуглеводнів (С8–С10); ? Аліфатичні смоли, отримані з фракції С5; ? Співолігомери, що поєднують компоненти С5 і С9; ? Циклоаліфатичні смоли, отримані з циклодиєнів (дициклопентадієну). Основні методи одержання НПС: 1. Олігомеризація в розчині – реалізується каталітичним (іонним) або радикальним способом. Іонна полімеризація здійснюється із застосуванням кислот (каталізатори Bronsted, Friedel–Crafts, цеоліти). Радикальна олігомеризація може бути термічною або ініційованою пероксидами. 2. Модифікація готових смол – шляхом введення функціональних груп або гідрування, що дозволяє змінювати колір, стабільність та розчинність продукту. 4 3. Дисперсійна олігомеризація – емульсійна й суспензійна. У емульсійній системі мономери емульгуються у воді за допомогою емульгаторів, а реакція відбувається за участі водорозчинного ініціатора. Цей метод дозволяє проводити процес при нижчих температурах, покращити тепловідведення й автоматизувати контроль, хоча потребує стадії коагуляції полімеру [4, 5]. Одержані продукти можуть використовуватися у: у лаках і фарбах – як плівкоутворювачі з доброю адгезією; у друкарських фарбах – як замінники каніфольних смол; у паперовій промисловості – для проклеювання; у гумових сумішах – як пластифікатори, сумісні з каучуками;у будівництві – як компонент мастик, герметиків, дорожніх покриттів. Використання побічних продуктів нафтохімії дозволяє зменшити витрати на виробництво полімерних матеріалів, підвищити ефективність використання ресурсів і сприяє екологізації хімічної промисловості. Мета роботи – дослідити синтез вуглеводневих смол із фракції С9, визначити їх реологічні властивості та розробити технологічну схему виробництва. Об’єкт дослідження – процес синтезу НПС з фракції С9. Предмет дослідження – методи коолігомеризації, властивості продуктів, технологічні режими. Розділ 1. Огляд літератури. У цьому розділі проаналізовано сучасні підходи до отримання НПС із фракцій РПП – зокрема С9, яка містить реакційно здатні мономери. Розділ 2. Описано методики експериментів та аналізів.. Розділ 3. Проведено аналіз реологічних властивостей трьох зразків НПС, визначено температурні коефіцієнти в’язкості, показники текучості, зміну напруження та швидкості зсуву. Установлено псевдопластичну природу смол. Виявлено, що смола стирен-циклопентадієнова є найбільш стабільною до змін температури, а стиренова смола – придатна до високонапружених середовищ (наприклад, каучуки чи бітумні суміші). 5 Розділ 4. Розроблено принципову схему періодичного процесу синтезу НПС, що включає стадії олігомеризації, атмосферної та вакуумної дистиляції. Розділ 5. Проведено розрахунок матеріального і теплового балансів процесу. .Визначено витратні коефіцієнти. Розділ 6. Розглянуто заходи з охорони праці Розділ 7. Визначено кошторис експериментальних досліджень.

This work presents research focused on the development of a technology for synthesizing hydrocarbon resins (HCRs) from the C9 fraction, a byproduct of hydrocarbon pyrolysis that contains aromatic, unsaturated components. The relevance of the study lies in the growing demand for import-substituting materials with improved performance properties, which are applicable in paint and varnish production, the rubber industry, paper manufacturing, and construction sectors [1, 2]. The main raw material for HCR production is liquid pyrolysis products, particularly the light fraction (up to 473 K), which includes valuable polymerizable components such as C5 and C9 hydrocarbons. It is noted that the content of active monomers (e.g., styrene, indene, dicyclopentadiene) in such fractions may reach 30–40 wt.%, making them a highly effective base for cooligomer synthesis [3]. Depending on the type of hydrocarbons in the feedstock, oligomers can be classified as: ? Aromatic resins, obtained from alkenyl-aromatic hydrocarbons (C8–C10); ? Aliphatic resins, derived from the C5 fraction; ? Cooligomers, based on combined C5 and C9 components; ? Cycloaliphatic resins, synthesized from cyclic dienes (e.g., dicyclopentadiene). The main methods for producing hydrocarbon resins include: ? Solution oligomerization – carried out via catalytic (ionic) or radical mechanisms. Ionic polymerization involves the use of acids (Bronsted catalysts, Friedel– Crafts systems, zeolites), while radical oligomerization may be thermally or peroxideinitiated. 7 ? Modification of finished resins – by introducing functional groups or by hydrogenation, which helps improve color, stability, and solubility of the product. ? Dispersion oligomerization – including emulsion and suspension techniques. In emulsion systems, monomers are dispersed in water with the help of emulsifiers, and polymerization is initiated by water-soluble initiators. This method enables processing at lower temperatures, ensures better heat removal, and allows for easier automation, although it requires an additional stage of polymer coagulation [4, 5]. The resulting hydrocarbon resins can be applied in various industries, including: Paints and varnishes – as film-forming agents with excellent adhesion; Printing inks – as rosin substitutes; Paper industry – as sizing agents; Rubber blends – as plasticizers compatible with elastomers; and Construction – as components in mastics, sealants, and asphalt formulations. Utilization of by-products from petrochemical processes reduces the production cost of polymer materials, increases resource efficiency, and contributes to the environmental modernization of the chemical industry. Research goal: to investigate the synthesis of hydrocarbon resins from the C9 fraction, evaluate their rheological properties, and design a production process flow scheme. Object of research – the synthesis process of hydrocarbon resins from the C9 fraction. Subject of research: oligomerization methods, product properties, and technological conditions. Chapter 1. This chapter analyzes modern approaches to the synthesis of hydrocarbon resins from pyrolysis products, particularly the C9 fraction, which contains reactive monomers suitable for oligomerization. Chapter 2. Describes the experimental setup, synthesis procedures, and analytical methods used to characterize the produced resins. Chapter 3. Presents the analysis of the rheological properties of three resin samples. Parameters such as temperature coefficients of viscosity, flow behavior, shear stress, and shear rate were determined. The resins exhibited pseudoplastic behavior. It was found that 8 the styrene–cyclopentadiene resin was the most thermally stable, while the pure styrene resin was best suited for high-stress environments (e.g., rubber or bitumen applications). Chapter 4. A process scheme was developed for the periodic synthesis of hydrocarbon resins, comprising oligomerization, atmospheric distillation, and vacuum distillation stages. Chapter 5. Material and thermal balances were calculated, including specific consumption coefficients for raw materials and energy carriers. Chapter 6. Outlines safety and labor protection protocols for the oligomerization department. Chapter 7. Presents a cost analysis of the experimental research and preliminary budgeting of the designed process.
Project of the C9 Fraction Oligomerization Department (Productivity of 7000 tons per year)
Keywords: 6.161.00.00; фракція С9; нафтополімерні смоли; коолігомеризація; ініціатор; реологія; температура розм’якшення; динамічна в’язкість. [1] Mildenberg; R.; Zander; M.; & Collin; G. (2008). Hydrocarbon resins. John Wiley & Sons. [2] Rahmatpour; A.; & Ghasemi Meymandi; M. (2021). Large-scale production of C9 aromatic hydrocarbon resin from the cracked-petroleum-derived C9 fraction: Chemistry; scalability; and techno-economic analysis. Organic Process Research & Development; 25(1); 120–135. [3] Zohuriaan-Mehr; M. J.; & Omidian; H. (2000). Petroleum resins: An overview. Journal of Macromolecular Science; Part C: Polymer Reviews; 40(1); 23–49. [4] Subtelnyy; R. O.; Zhuravskyi; Y. V.; & Dzinyak; B. O. (2023). Suspension oligomerization of C9 hydrocarbon fraction initiated by aliphatic N-substituted aminoperoxides. Voprosy Khimii i Khimicheskoi Tekhnologii; (4); 105–112. http://dx.doi.org/10.32434/0321-4095-2023-149-4-105-112 [5] Fuch; U.; Dzinyak; B.; & Subtelnyy; R. (2015). Study of emulsifier nature effect on the process of hydrocarbon fraction cooligomerization in the emulsion. Eastern-European Journal of Enterprise Technologies; 4(6); 54–57. https://doi.org/10.15587/1729- 4061.2015.47205; C9 fraction; hydrocarbon resins; cooligomerization; initiator; rheology; softening point; dynamic viscosity. [1] Mildenberg; R.; Zander; M.; & Collin; G. (2008). Hydrocarbon resins. John Wiley & Sons. [2] Rahmatpour; A.; & Ghasemi Meymandi; M. (2021). Large-scale production of C9 aromatic hydrocarbon resin from the cracked-petroleum-derived C9 fraction: Chemistry; scalability; and techno-economic analysis. Organic Process Research & Development; 25(1); 120–135. [3] Zohuriaan-Mehr; M. J.; & Omidian; H. (2000). Petroleum resins: An overview. Journal of Macromolecular Science; Part C: Polymer Reviews; 40(1); 23–49. [4] Subtelnyy; R. O.; Zhuravskyi; Y. V.; & Dzinyak; B. O. (2023). Suspension oligomerization of C9 hydrocarbon fraction initiated by aliphatic N-substituted aminoperoxides. Voprosy Khimii i Khimicheskoi Tekhnologii; (4); 105–112. http://dx.doi.org/10.32434/0321-4095-2023-149-4-105-112 [5] Fuch; U.; Dzinyak; B.; & Subtelnyy; R. (2015). Study of emulsifier nature effect on the process of hydrocarbon fraction cooligomerization in the emulsion. Eastern-European Journal of Enterprise Technologies; 4(6); 54–57. https://doi.org/10.15587/1729- 4061.2015.47205